PEMBATALAN KUNJUNGAN PRESIDEN SUSILO BAMBANG YUDHOYONO KE BELANDA TAHUN 2010 - Ressa Endar Saputri (2011)
This thesis tries to elaborate the cancelation of President Susilo Bambang Yudhoyono's visitation to Holland at 2010. Generally, Indonesia-Holland's are increasing relationship. Indonesia-Holland agreed to upgrade Indonesia-Holland's relationship status, both of these countries agreed to sign in "Comprehensive Partnership Agreement". Comprehensive Partnership Agreement was schedule since 2007 and the program will be happen at October 6th-9th 2010. Queen of Holland invite President of Indonesia S